2020
DOI: 10.24843/spj.2020.v08.i02.p12
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Muscle Energy Technique in Individuals With Mechanical Neck Pain: A Systematic Review

Abstract: Introduction: Mechanical neck pain is a condition that includes minor strain / sprain in the muscles, ligaments, or facet joint dysfunction. Objective: This systematic review is aimed to find out the effectiveness of the muscle energy technique in mechanical neck pain. Method: The systematic review access to journal databases such as: PubMed, PEDro, and the Cochrane Library. Results: Based on inclusion and exclusion criteria 5 articles were used in this systematic review. The application of the muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another study that examined the benefits of the post-isometric relaxation technique on mechanical neck pain came to the conclusion that MET greatly decreased pain and enhanced day-to-day functioning [5]. Similarly, a study found that MET is successful in reducing pain and increasing the range of motion [12][13][14]. There was a…”
Section: Discussionmentioning
confidence: 99%
“…Another study that examined the benefits of the post-isometric relaxation technique on mechanical neck pain came to the conclusion that MET greatly decreased pain and enhanced day-to-day functioning [5]. Similarly, a study found that MET is successful in reducing pain and increasing the range of motion [12][13][14]. There was a…”
Section: Discussionmentioning
confidence: 99%
“…The technique employed was post-isometric relaxation (PIR), a MET belonging to the TEM group, follow-ing the principles developed by Mitchell. According to these principles, after an isometric muscle contraction with a force not exceeding 30% of the maximum force and a duration of 5-7 seconds, a passive elongation was introduced to a new tissue barrier position [5]. For each muscle, the sequence was repeated three times, and the final achieved position was maintained for 30 seconds.…”
Section: Interventionsmentioning
confidence: 99%
“…Studies have been conducted on the effectiveness of MET in various diseases such as cervicalgia [ 18 , 19 , 20 ], chronic low back pain [ 21 ], chronic obstructive pulmonary disease (COPD) [ 22 ], and symptomatic and asymptomatic subjects [ 23 ]; however, studies on the hamstring have not been reported. Furthermore, studies of static stretching [ 24 ], Nordic hamstring exercise [ 25 , 26 , 27 ], eccentric training [ 28 , 29 ], and strength training [ 30 ] have been reported on the effects of hamstring strength and flexibility, but no comparative studies with MET have been published.…”
Section: Introductionmentioning
confidence: 99%